ANALISIS FAKTOR KUALITAS PRODUK DAN JASA PELAYANAN TERHADAP TINGKAT KEPUASAN KONSUMEN PIA SINAR ABADI BALI - Angeline Liu, Chintya; Hartiati, Amna; Anom Yuarini, Dewa Ayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 3 (2015): September)
Product quality and service have been the best method to compete that is used in the trade and service industry. One of the efforts that can be used to improve, maintain, and compete in a company is to increase the consumer satisfaction. The objectives of this study are to determine 1) a partial relationship of products quality on the level of consumer satisfaction 2) a partial relationship of services to the level of consumer satisfaction 3) and the simultaneous relationship of the quality of products and services on consumer satisfaction. The method of collecting data in this study was the 270 questionnaires distribution. Factor analysis, partial correlation, and simultan correlation method was used to analyze partially and simultaneous a relationship between the quality of the product (X1), service (X2), and consumer satisfaction (Y). According to see partial correlation analysis, is known that the value of correlation between product quality and customer level of satisfaction is 0.524 which indicates that there is slightly weak relationship between product’s quality and the customer’s satisfaction level if the services is steady. The value of correlation between the services and customer’s satisfaction level is 0.757 which indicates that there is a strong relationship between service and customer’s satisfaction if the quality of the product is steady. Simultaneous correlation value is known that the correlation between the quality of product and service to the customer’s satisfaction level is 0.875. This value indicates that the relationship between the quality of products and services to the customer’s satisfaction level is very strong.
Keywords: 54,